Nanotechnology-Based Celastrol Formulations and Their Therapeutic Applications - Wagh, Pushkaraj Rajendra; Desai, Preshita; Prabhu, Sunil; Wang, Jeffrey (Frontiers in Pharmacology, 2021)
Celastrol (also called tripterine) is a quinone methide triterpene isolated from the root extract of Tripterygium wilfordii (Thunder God Vine in traditional Chinese medicine). Over the past two decades, celastrol has gained wide attention as a potent anti-inflammatory, anti-autoimmune, anti-cancer, anti-oxidant, and neuroprotective agent. However, its clinical translation is very challenging due to its lower aqueous solubility, poor oral bioavailability, and high organ toxicity. To deal these issues, various formulation strategies have been investigated to augment the overall celastrol efficacy in vivo by attempting to increase the bioavailability and/or reduce toxicity. Among these, nanotechnology-based celastrol formulations are most widely explored by pharmaceutical scientists worldwide. Based on the survey of literature over the past 15 years, this mini-review aims at summarizing multitude of celastrol nanoformulations that have been developed and tested for various therapeutic application. In addition, the review highlights unmet need in the clinical translation of celastrol nanoformulations and the path forward.